Nanotubos de carbono em associação com coletores na flotação catiônica reversa de minério de ferro - Delciane Porfiro (2019)
Flotation is a separation method known for more than 100 years. Regarding iron ore, studies on its application were started in the 1930s. Since 1930s research on the direct anionic flotation of iron oxides, reverse anionic flotation and reverse cationic flotation of quartz has been conducted. In Brazil the iron ore miners use in their concentrators, which are fed with increasingly lower grade ores, reverse cationic quartz flotation to obtain pellet feed. Industrially, quartz is floated using etheramines, partially neutralized with acetic acid, as collector. The use of efficient and effective collectors is a critical point for improving the performance of the flotation process. Studies have shown that for collectors with a specific hydrophilic portion the increase on the length of the hydrocarbon chain leads to greater flotation efficiency due to, for instance, reduction of the surface tension of the system. On the other hand, amines with lengthy hydrocarbon chains have higher hydrophobic portions and lower solubility degrees. Partial replacement of amine or association with other substances has been evaluated in the search for better performance of the collectors and, consequently, of the process. The application of carbon nanomaterials functionalized with surfactants for the recovery of metallic ions in environmental processes has been proved feasible. The aim of this investigation was to evaluate the recovery of quartz in modified Hallimond tube and flotation tests on bench scale using commercial amine associated with functionalized carbon nanomaterials. The use of functionalized carbon nanomaterials added directly to amine affected quartz floatability in different ways, resulting in either increased and decreased recovery in the floated fraction when compared with amine added individually. These antagonistic effects resulted from the amount of carbon nanomaterials added to amine. The results indicated that the functionalized nanomaterials interacted with amine originating a distinct chemical species.